2015
DOI: 10.4103/2230-8598.151270
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in bronchial asthma patients

Abstract: Introduction: Asthma is a common chronic disease that affects persons of all ages. People with asthma report impact on the physical, psychological and social domains of quality of life. Health-related quality of life (HRQoL) measures have been developed to complement traditional health measures such as prevalence, mortality and hospitalization as indicators of the impact of disease. Objective and Study Design: The objective of this study was to assess HRQoL in Bronchial asthma patients and to relate the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Our patient population age and male-to-female ratio were similar to the demographics of similar studies reported by Gonzalez-Barcala [10] and Nalina and Chandra [17].…”
Section: Discussionsupporting
confidence: 88%
“…Our patient population age and male-to-female ratio were similar to the demographics of similar studies reported by Gonzalez-Barcala [10] and Nalina and Chandra [17].…”
Section: Discussionsupporting
confidence: 88%
“…It is estimated that about 40% of all young children have at least one episode of asthmatic symptoms like wheezing, coughing, and dyspnea [21]. People with asthma report impact on the physical, psychological and social domains of quality of life [22]. The Pediatric asthma quality of life questionnaire (PAQLQ) is fully validated to be used in both clinical trials and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although allergies have been repeatedly shown to have a significant and continuing impact on health‐related quality of life, the majority of the research so far is focused on individuals with one allergic comorbidity and based on parental reports …”
Section: Introductionmentioning
confidence: 99%